On the dislocation-oxygen interactions in Czochralski-grown Si: oxygen diffusion and binding at low temperatures - Senkader, S; Giannattasio, A; Falster, R; Wilshaw, P (2002)
The interaction between oxygen atoms and dislocations in Czochralski-grown silicon has been studied experimentally. Measurements concerning the locking of dislocations by oxygen atoms have been carried out in the temperature range 450-850degreesC for different annealing times Using samples with low oxygen content (2.6 x 10(17) cm(-3)) it has been possible to investigate the nature of binding of oxygen atoms to dislocations for temperatures lower than 700 degreesC for which diffusion of oxygen in silicon has well known 'anomalous' behaviour. It has been found that although the binding enthalpy for temperatures larger than 700 degreesC agrees well with the previously published value, its value is different for lower temperatures. We measured the oxygen-dislocation binding enthalpy to be about 0.2 eV in the temperature range of 450-650degreesC.